Emotional intelligence and aggression in the secondary educational levels - GUERRERO CARRANZA, Virginia Rosemary (2020)
The objective of this study was to analyze the relationship between emotional intelligence and aggressionin high school students. A sample of 567 students (men and women) from 12 to 17 years of age from fivestate educational institutions of the city of Trujillo was randomly selected. In that sense, they were appliedthe Aggression Questionnaire (AQ) of Buss and Perry and the Emotional Intelligence Inventory of Bar-On.The results show the existence of significant and inverse correlation of emotional intelligence with aggression in general and its factors (verbal aggression, physical aggression, hostility and anger) Keywords: Emotional intelligence, aggr ession, hostility.